If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -3y + 8 + -8 = 5y + -12 Reorder the terms: 8 + -8 + -2y + -3y = 5y + -12 Combine like terms: 8 + -8 = 0 0 + -2y + -3y = 5y + -12 -2y + -3y = 5y + -12 Combine like terms: -2y + -3y = -5y -5y = 5y + -12 Reorder the terms: -5y = -12 + 5y Solving -5y = -12 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -5y + -5y = -12 + 5y + -5y Combine like terms: -5y + -5y = -10y -10y = -12 + 5y + -5y Combine like terms: 5y + -5y = 0 -10y = -12 + 0 -10y = -12 Divide each side by '-10'. y = 1.2 Simplifying y = 1.2
| 5-5n=14-8n | | 9-3x=2x-11 | | 2c-12=-2c | | 2x-3x=x | | x+(5+x)+(9+x)=59 | | X^2+2x+29=0 | | 23=k-0.7 | | 2x+6=16-3x | | 7b+11=11+7b | | x^2+27x+177=0 | | b+2.5=1 | | 3y+2x=21 | | 2(8h)=16(6h) | | x^2-6x+27=0 | | 22x^2-1=0 | | 4d+8d=1-27 | | Y=-5(2x-3) | | =0+10-8+2 | | 4p/7=7-9+6 | | 3a+7=4 | | 5x-11-4x+24=5 | | u-9=4u+15 | | 16x^6+8x^6=0 | | y=x^2-4x-60 | | 10-2n=3n-20 | | m(n)=m+n | | -6v=-12b | | 29=33.3+7 | | 0=ln(2x+5)*ln(9x^2) | | 8-2n-14=-27-9n | | 1.8x=0.9 | | -27=8+7x |